FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIFITAS KARYAWAN DEPARTEMEN STAMPING PERUSAHAAN DALAM INDUSTRI PENGOLAHAN KENDARAAN BERMOTOR - RR. NIKEN PURBASARI; R. WASISTO RUSWIDIONO; FARADILA Y. ARDINI (Media Bisnis, 2020)
The success of manufacturing companies managing employee productivity will determine the company's continuity in maintaining its position in the manufacturing industry. This study aims to determine the effect of compensation, work discipline and intrinsic motivation on employee productivity of the stamping department of PT MXX, which is one of the major companies in the motor vehicle processing industry in Indonesia. Using saturated sampling techniques, the total population in this study was 118 employees. The analytical method used is multiple linear regression. The results of this study indicate that only compensation that affects employee productivity, work discipline and intrinsic motivation does not affect the productivity of PT MXX employees which may be caused by the characteristics of the work characteristics of the stamping department and the characteristics of the population dominated by male sex employees with young adults who emphasize the meaning the importance of the compensation they receive as a result of their work productivity